La mobilité des sociétés de l’espace OHADA : étude à la lumière du droit européen et international des sociétés. - Sane, Claude MIchel (Université de Pau et des Pays de l'Adour, 2017)
À coté de l’objectif immédiat d’uniformiser les législations des États membres, l’OHADA s’est fixée un objectif médiat, celui de créer un vaste marché sans frontière. Or au regard des difficultés pour les sociétés commerciales de déplacer leurs sièges sociaux d’un État membre à un autre, nous ne pouvons que constater que l’existence de ce marché intégré n’est pas encore une réalité pour elles. Il apparaît alors que la seule uniformisation du droit des sociétés commerciales par l’OHADA ne suffit pas à leur permettre de réaliser des opérations de restructuration transfrontalière. Cette thèse a ainsi montré que l’OHADA a besoin d’évoluer et de se transformer pour mettre en place un véritable droit à la mobilité pour les sociétés commerciales au sein son espace communautaire. Elle doit pour cela compléter son intégration juridique par une intégration économique consacrant un libre établissement dont les opérations de mobilité seraient des modalités d’exercice, comme l’a fait l’Union européenne. Ce droit à la mobilité ne devra toutefois pas s’exercer de manière abusive. L’OHADA devra donc trouver un équilibre entre une mobilité fluidifiée et une protection efficace des actionnaires, salariés et tiers. De même il conviendra de rechercher un équilibre dans la gestion de la coexistence des normes communautaires qui ne manquera pas de se présenter dans le régime des opérations de mobilité puisqu’il s’agit d’un problème récurrent dans l’espace OHADA. Apart from the direct objective of the Organization for the Harmonization of Business Law in Africa (OHADA) to standardize the law, its indirect objective relates to the creation of a large common market. However, regarding the difficulties for companies to transfer their registered office from one member state to another, we can see that the existence of such market is still not a reality for them. Therefore, it appears that the only standardizing of the corporate law by OHADA is not sufficient to allow them to perform their cross-border mergers. This research shows thus that OHADA needs to change and to transform itself to put in place a real right to mobility in the community area for the companies. Like the European Union, it should complete the legal integration by an economic integration setting up a freedom of establishment, including border restructuring operations. But this right to mobility should not be abused. OHADA will have to find a balance between facilitating the mobility and protecting efficiently minority shareholders, employees and third parties rights. Similarly a balance must be struck to solve the conflict of community norms in the restructuring operations legal regime, since it is a recurrent problem for OHADA space.
Keywords: Border reorganization; Border transfer of registered office; Companies freedom of establishment; Conflict of community norms; Conflit de normes communautaires; Corporate law; Cross-border mergers; Droit commercial (droit international); Droit communautaire africain; Droit communautaire européen; Droit des sociétés; Droit européen; Droit international des sociétés; Droit international privé (droit européen); Economic integration; European and African community law; Fusion transfrontalière; International corporate law; Intégration juridique; Intégration économique; Legal integration; Libre établissement des sociétés; Nationality of companies; Nationalité des sociétés; Organisation pour l’harmonisation en Afrique du droit des affaires; Organization for the Harmonization of Business Law in Africa (OHADA); Restructuration transfrontalière; Sociétés; Transfert transfrontalier de siège social

La protection des associés et des créanciers dans les opérations de fusion et d’apport partiel d'actif des sociétés commerciales en droit français et en droit OHADA - Wagou Leumega, Marie Pamela (Université de Lorraine, 2017)
La fusion et l’apport partiel d’actif soumis au régime des scissions sont des opérations fréquentes tant en France que dans les pays membres de l’OHADA. Elles présentent des risques multiples pour les actionnaires et les créanciers et cette thèse s'attache justement à étudier la protection qui s'offre à ces catégories. Cette étude fait apparaître que leur protection est assurée par trois éléments essentiels dans les deux ordres juridiques : l'information, la consultation et le principe de la transmission universelle du patrimoine. Nos analyses révèlent cependant que ces protections sont insuffisantes car elles ne sont pas mises en œuvre de manière optimale et sont fortement limitées par la jurisprudence. Aussi pour améliorer le système actuel, des solutions législatives et contractuelles sont nécessaires pour garantir au mieux la protection des actionnaires et des créanciers. La voie législative permet de renforcer l’efficacité d’un droit, comme par exemple la reconnaissance du droit de retrait aux actionnaires. Quant à la contractualisation, elle permet de renforcer la protection de base instituée par les textes, ainsi que l’illustre la clause de survie de l’obligation de couverture ou de la garantie autonome. The merger and the partial contribution of assets subjected to the regime of splits are frequent operations both in France and in the member countries of the OHADA. They present multiple risks for shareholders and creditors, and this thesis focuses on the protection afforded to these categories. This study shows that their protection is ensured by three essential elements in the two legal orders: information, consultation and the principle of the universal transmission of the heritage. However, our analyzes reveal that these protections are insufficient because they are not implemented optimally and are strongly limited by case law. To improve the current system, legal and contractual solutions are needed to ensure the best protection of shareholders and creditors. The legislative way makes it possible to reinforce the effectiveness of a right, as for example the recognition of the right of withdrawal to the shareholders. As for the contractualization, it makes it possible to reinforce the basic protection instituted by the texts, as the survival clause of the obligation of cover or of the autonomous guarantee illustrates it.
Keywords: Apport partiel d’actif; Associates; Associés; Creditors; Créanciers; Droit commercial; Fusion; Fusion d'entreprises; Merger; Partial asset contribution

L’action civile de l’associé en droit pénal des sociétés - Martinelle, Mathieu (Université de Lorraine, 2017)
La victime en col blanc est mésestimée, tant par l’opinion publique que par le droit. Si les infractions en matière économique, financière et boursière heurtent, les personnes lésées par ces agissements bénéficient peu de l’empathie traditionnellement accordée aux victimes pénales. Parmi elles, il en est cependant une qui mérite une attention particulière : l’associé. Alors qu’une personne sur trois dispose en France de cette qualité, l’associé est susceptible d’être une victime du fait de son engagement. Acteur social majeur, il peut subir les effets d’une infraction au droit pénal des sociétés. Lorsqu’il est la victime d’une telle infraction, l’associé a vocation à exercer une action civile. Action en réparation appartenant à tous ceux ayant subi un dommage directement causé par l’infraction, celle-ci est toutefois réservée aux seuls associés titulaires du bien juridique protégé par l’incrimination chef des poursuites. Alors que le droit d’agir en action civile de l’associé est ainsi limité, le bien-fondé de la demande en réparation de son préjudice est également soumis à des conditions interprétées à l’aune de théories singulières. Le brouillard dans lequel se situe aujourd’hui l’associé victime d’une infraction au droit pénal des sociétés est dense. Il nous revient de l’en sortir en proposant des évolutions conformes au droit et répondant à la situation réelle de cette victime pénale jusque-là oubliée.
Keywords: Action civile; Associé; Bearer of the protected legal interest; Bien-fondé; Business criminal law; Civil proceedings; Compensation; Corporate law; Dommages-intérêts; Droit de la réparation; Droit des sociétés; Droit d’agir; Droit pénal des sociétés; Indemnisation; Partner; Poursuites judiciaires; Préjudices réparables; Repairable injuries; Right of action; Right to compensation; Titulaire du bien juridique; Validity

Le contrôle de la gestion des sociétés commerciales : approche systémique - Nicolas-Belizon, Delphine (Aix-Marseille Université, 2017)
Les sociétés commerciales sont un des piliers de l’économie française. Génératrices de richesses, il est important d’assurer leur bon fonctionnement. Selon la tradition française, les dirigeants sociaux sont seuls maîtres aux commandes de la gestion et disposent à cette fin des pleins pouvoirs. Si cette hégémonie est un gage de performance et de dynamisme économique, cette prévalence des dirigeants est aussi porteuse de risques. La bonne santé des sociétés et leur pérennité sont directement influencées par les agissements des dirigeants. Le besoin de contrôler la gestion de ces derniers n’est donc plus à démontrer. En revanche, la question de la réalité du contrôle se pose aujourd’hui. L’étude du contrôle des sociétés commerciales conduit à poser la théorie selon laquelle le droit a érigé un véritable système. En effet, le droit des sociétés appréhende la question du contrôle dans sa globalité. A ce titre, un contrôle conventionnel complète un contrôle légal relativement perfectionné. Pour cause, au-delà des instruments juridiques à disposition des contre-pouvoirs, les conditions du contrôle et ses conséquences sont également prises en compte par le législateur. D’ailleurs, l’imbrication entre ces différents éléments confirme l’intérêt d’une approche systématique du contrôle des sociétés commerciales. L’attention du législateur portée à ce système depuis plusieurs décennies le rend aujourd’hui pour le moins efficace. Si certaines réserves demeurent, le droit des sociétés permet un contrôle satisfaisant de la gestion des dirigeants. Commercial companies are one of key players of the French economy. Wealth generating, it is important to ensure their smooth operation. According to french habits, social leaders are the only masters in charge of management and have full powers. While this dominance is a success’ key factor and ensures economic dynamism, this omnipotence may carry potential risks. Good health and sustainability of companies depend directly on leaders’ decisions. Unnecessary to demonstrate it, we need to monitor their management. In return, reality of monitoring could also be asked today. The study of commercial companies’ monitoring requires to analyze legal basis which arises this system. Indeed, business law is based on overall control. For this reason, a conventional audit completes a rather sophisticated legal audit. As a result, beyond legal instruments in the hands of opposition, monitoring conditions and its consequences are also taken into account by the legislator. Besides, the imbrication of these different points confirms the interest of a systematic approach to check commercial companies. The legislator's attention to this particular system has proved to be effective since many years. Even if certain reservations remain, business law gives satisfaction regarding top management monitoring.
Keywords: Audit; Contrôle de gestion; Corporate law; Droit des sociétés; Droit des sociétés commerciales; France

L'agrément en droit des sociétés : contribution à une simplification du droit - Le Ruyet, Armel (Université de Rennes 1, 2017)
L’étude de l’agrément en droit des sociétés révèle que les règles l’encadrant ne sont pas exemptes de lacunes ou d’incohérences. Ces dernières résultent notamment de leur édiction dispersée, dans des textes légaux ou réglementaires, au cas par cas, individuellement pour chaque forme sociale. En outre, leur intelligibilité est amoindrie par la corrélation parfois faite par la loi entre les règles de son domaine et ses formalités procédurales. De cet ensemble découle une certaine complexité, incompatible avec le besoin de sécurité juridique requise pour exécuter toute procédure. En l’occurrence, l’atteinte à la liberté ne réside plus dans l’absence de forme protectrice mais, paradoxalement, dans un formalisme trop pointilleux, dont l’application suscite un important contentieux. Néanmoins, le constat de la présence éventuelle de l’intuitu personae dans l’ensemble des sociétés suggère la possibilité d’unifier le domaine de l’agrément et, corrélativement, de simplifier sa mise en œuvre, grâce à l’élaboration d’un droit commun. À cette fin, une conception contractuelle des rapports sociaux donne de nombreuses clés de résolution des problèmes posés actuellement par son régime. Cette analyse faite du droit positif ne remet pas pour autant en cause le juste équilibre établi par la loi au nom de l’ordre public sociétaire. Celui-ci s’exprime par l’exigence du respect de formalités et d’obligations visant à protéger tant la société que son associé cédant. Au contraire même, ce point de vue permet de dégager les champs d’intervention réservés au législateur ne portant atteinte ni à la substance des droits de l’associé, ni aux concepts juridiques de droit commun. Cette méthode de traitement des difficultés soulevées aboutit à une reconstruction de la législation de l’agrément, davantage intelligible, augurant par là-même, une perspective concrète de création d’un droit français des sociétés fermées.
Keywords: Associates; Associés; Autorisations; Cession de contrat; Common interest; Conflict of interest; Conflit d’intérêts; Contract-Organization; Contrat de société; Contrat-Organisation; Corporate law; Droit des sociétés; Décision sociale; Formalism; Formalisme; France; Intuitu personae; Intérêt commun; Ordre public sociétaire; Partnership agreement; Private companies; Procedure; Procédure; Public corporation order; Simplification; Social decision; Sociétés fermées; Transfer of contract; Transfers of social rights; Transferts de droits sociaux

Etude critique des modes de cession applicables au fonds de commerce dans le cadre de la réalisation des actifs en liquidation judiciaire - Bourdais, Matthieu (Université Lille 2, 2017)
Depuis la réforme du droit des procédures collectives par la loi de sauvegarde des entreprises du 26 juillet 2005, deux régimes de cession aux conséquences juridiques dissemblables restent applicables lors des réalisations d’actifs en liquidation judiciaire. Le fonds de commerce, bien particulier à la définition lacunaire, présente la particularité d’être éligible tant à l’application du régime de la cession d’entreprise des articles L 642-1 et suivants du Code de Commerce, qu’à celle de la cession de biens isolés de l’article L 642-19 du Code de Commerce. Les éléments guidant la répartition des ensembles cédés sous l’un ou l’autre régime restent cependant à ce jour imprécis, compromettant la sécurité juridique des différents acteurs de la procédure. Suite à l’étude des causes théoriques et pratiques de cette confusion, des propositions de réforme de ces régimes peuvent être formulées afin d’offrir aux intervenants à la procédure, qu’ils soient parties à la cession, créanciers, ou salariés, une meilleure lisibilité de leurs droits et obligations = Since the reform of the collective procedures by the July 26, 2005 Companies backup Act, two regimes of sales, of dissimilar legal consequences, can be applied during the divestments of the assets that takes place in the final stages of the judicial liquidation. The goodwill, specific asset of lacunar definition, has the particularity to be eligible both for the application of the system of transfer of companies mentionned at the article L 642-1, to that of isolated assets divestment regime mentionned at the article article L 642-19 of the French Commercial Code. Elements guiding the distribution of sets sold under one or the other regime remain however to this day unclear, compromising the legal security of the different actors in the process. Following the study of the theory and practice of this confusion causes, proposals for reform of these regimes can be formulated to provide to the participants in the proceedings, may they be parties to the sales, creditors or employees, a better readability of their rights and obligations
Keywords: Cession de biens isolés; Cession de l’entreprise; Company; Company transfer regime; Entreprise; Entreprises (disparition); Fonds de commerce; Fonds de commerce - France; France; Goodwill; Isolated assets divestment regime; Judicial liquidation; Liquidation Judiciaire; Redressement judiciaire

Legal framework of Directors' Duties in OHADA Law (Senegal) - Niang, Oumar (International Journal of Business, Economics and Management Works, 2017)
This article is aimed to study the legal framework of directors’ duties in Ohada law. The Organization for the Harmonization of Business Laws (OHADA),is a supranational system of business laws that, as implemented in Senegal is trying to regulate all the core businesses.Ohada displays two level of mixing.Firstly,Ohada Law is supranational, it becomes part of the internal law of each state member but still remains supranational characteristics.Secondly,Ohada being at least partially French-inspired, we can  understand that the most of the countries which adopted Ohada Laws are French-speaking. The duties of Directors in Senegal are regulated mainly by the uniform companies’ act which is part of the Ohada law. It should be noted that before the adoption of Ohada, company law was governed by the code of civil obligations and in its fourth part. For companies listed on the RSE, they must comply both with the general regulations of the BRVM and with the provisions of the Uniform Companies Act concerning publicly traded companies. This article aims to illuminate the lanterns on the question of the duties of directors in Ohada law, during my research I have observed that subjects such as corporate governance in general and the duties of directors in Ohada are left stranded by most researchers. This is why this topic has an interest in reabsorbing this gap insofar as the legal framework of the duties of directors often mentions many questions because of the lack of loyalty and diligence of certain directors.
Keywords: Company law; Corporate; Directors Duties; Governance; Senegal

La médiation interentreprises dans le monde francophone - Henry, Sophie (La lettre des médiations, 2017)
Concurrence déloyale, inexécution contractuelle, rupture brutale, conflit entre associés… Autant d’exemples de litiges qu’une entreprise peut être amenée à connaître au cours de son existence. La longueur et le coût des procédures, l’aléa et le carcan d’une décision de justice obligent les entreprises à repenser leur politique de gestion des conflits, Leurs contraintes économiques favorisent progressivement les modes amiables de règlement. Elles optent de plus en plus pour la médiation, dans une perspective d’efficacité, d’optimisation des coûts et délais et de maîtrise de leur image. Dans une étude réalisée en 2016 par le CMAP (Centre de Médiation et d’Arbitrage Paris) en partenariat avec Squaremic et Baro Alto, il apparait que 90% des entreprises interrogées ont eu recours à la médiation au moins une fois sur les douze derniers mois et 77% d’entre elles jugent ce mode de résolution efficace.
Keywords: Gestion de conflits; Mediation; Médiation

Etude de la performance de la coopétition par le capital social : le cas des mines artisanales de diamant au Kasai, en République Démocratique du Congo - Ngidjima Loleke Lotshangola, Jose (Université de Limoges, 2017)
Dans une économie globalisée actuelle, où l’environnement entrepreneurial est défini comme incertain et turbulent, les entreprises choisissent les stratégies de coopétition pour avoir des avantages et performances. Mais, selon la littérature spécialisée, si les avantages et les performances, sont mis en avant pour justifier la pertinence des stratégies de coopétition, la notion d’opportunisme du partenaire est elle aussi largement investie et identifiée par des recherches comme un frein à la coopétition. C’est de cette façon, qu’on peut constater dans cette littérature, deux thèses différenciées qui caractérisent les analyses sur la coopétition ; une relation entre concurrents, source de performances hors normes et une relation fragile et instable à tout instant, à raison de l’opportunisme présumé du partenaire. L’opportunisme du partenaire s’avère particulièrement problématique en ce qu’il conduirait à limiter les performances et avantages attendus de la coopétition. L’objectif de cette recherche est d’établir un lien entre la performance de la coopétition et le capital social. Partant de l’opportunisme du partenaire, nous avons posé que la performance d’une coopétition est fonction de deux préalables : la réduction de l’opportunisme et l’augmentation de l’engagement des acteurs en relation. Une étude empirique est menée auprès des coopétitions des TPE minières exploitant le diamant au Kasaï, en République Démocratique du Congo. Une méthodologie qualitative permet le recueil des données par entretiens semi-directs, puis l’exploitation des termes des discours en se servant de l’outil lexicometrique, « Iramuteq ». L’objectif est de repérer les éléments déterminés de manière théorique, et qui traduisent soit les enjeux de la coopétition pour les TPE d’un environnement difficile, soit la pertinence du capital social dans la performance de la coopétition. Des liens établis entre la réduction de l’opportunisme, l’augmentation de l’engagement et les avantages tirés de la coopétition avec le capital social, constituent l’apport de cette recherche. Apport qui concerne les connaissances tant en management de la coopétition, que relatives aux TPE de contexte difficile. La variable-clé, « opportunisme » du partenaire, est la source du lien constaté entre la performance de la coopétition et le capital social. La logique suivie se décline en réponse aux interrogations formulées dans la littérature par différents auteurs au sujet de l’opportunsme qui conduit à la fragilité et à l’instabilité de la coopétition. Ce qui nous autorise de formuler un modèle vertueux de la performance de la coopétition par le capital social. A l’issu de notre étude empirique, une discussion sur des implications managériales est menée, aboutissant à une forme spécifique de coopétition mobilisant deux niveaux de réseau et des préconisations sont envisagées. In today’s global economy, where the entrepreneurial environment is defined as uncertain and turbulent, companies choses coopétition strategies to have advantage and performance. But, according to the specialized literature, if the advantage and the performance are highlighted to justify the relevance of the strategies of coopetition, the notion of opportunism of the partner is also widely invested and identified by research as a brake on coopetition. It is in this way that we can see in this literature two differentiated theses which goods the analyses on coopetition; a relationship between competitors, a source of exceptional performance and a fragile and unstable relationship at all times, on account of the supposed opportunism of the partner. The opportunism of the partner is particularly problematic in that it would lead to limiting the performance and advantages from expected coopetition. The aim of the research is to establish a link between the performance of coopetition and social capital. Based on the opportunism of the partner, we have posited that the performance of a coopetition depends on two prerequisites: the reduction of opportunism and the increase in the commitment of the actors in relationships. Year empirical study is being carried out on the coopetition of very small mining companies of diamond in kasaï in Democratic Republic of Congo. A qualitative methodology allows the collection of data by semi direct interviews and the operation of the terms of speech using the lexicon metric tool “Iramuteq”. The objective is to identify the theoretically determined elements, which reflect either the stakes of coopétition for very small mining companies in a difficult environment or the relevance of social capital in the performance of coopetition. The link between the reduction of opportunism, the increase in commitment and the advantages of coopetition with social capital are the contribution of the research, contribution that concerns the knowledge both in management if coopetition, and relating to the very small mining companies of difficult context. The key variable “opportunism” of the partner is the source of the link between the performance of coopetition and social capital. The logic followed us in response to the questions raised in the literature by different authors about the risk of opportunism that leads to the fragility and instability of coopetition. This allows us to formulate a virtuous model of the performance of coopetition through social capital. At the end of our empirical study, a discussion on managerial implications is conducted; leading to a specific form of coopetition invoicing two levels of network and recommendations are envisaged.
Keywords: Capital social; Coopétition; Diamant; Difficult environment; Environnement difficile; Kasaï (Congo, République démocratique); Opportunism; Opportunisme; Très petite entreprise; Very small company

L'inégalité entre associés en droit des sociétés - Ndiaye, Momath (Université Paris 1, 2017)
Initialement, le droit des sociétés était dominé par un principe général d'égalité. Par conséquent, la discrimination entre associés n'était admise que de façon exceptionnelle. Cette situation a, toutefois, évolué sous l'effet conjugué de deux phénomènes. D'une part, doctrine et jurisprudence s'accordent depuis longtemps à admettre que l'égalité entre associés n'a qu'une portée relative. Celle-ci doit s'apprécier in concreto et ne s'oppose pas aux traitements inégalitaires entre associés justifiés par la défense de l'intérêt social ou l'existence de différences de situations. D'autre part, le législateur a progressivement introduit dans le droit des sociétés de nombreux mécanismes ayant une fonction inégalitaire. Il en était ainsi des anciennes catégories d'actions, en l'occurrence les actions de priorité, celles à dividende prioritaire sans droit de vote, des certificats d'investissement ou de vote. Il en est de même des actions de préférence et des avantages particuliers. Tous ces dispositifs ont pour vocation de rompre l'égalité entre associés, en procurant à certains, des privilèges non partagés par les autres. Pourtant, la loi permet, ou permettait, largement leur instauration. Au regard de ces observations, il était devenu légitime de s'interroger sur l'existence d'un droit de discriminer entre les associés.L'ambition de cette étude est de démontrer que l'inégalité entre associés bénéficie d'une validité générale dans les sociétés. En clair, construire une définition, déterminer ses fondements juridiques, les possibilités et les limites ainsi que la procédure de sa création et de sa disparition, tels sont les éléments qui devaient être apportés à la réflexion juridique afin de permettre aux praticiens d'aborder la discrimination entre associés avec plus de sérénité. Initially, corporate law was dominated by a general principle of equality. Consequently, discrimination between partners was admitted only exceptionally. This situation, however, evolved under the combined effect of two phenomena. On the one hand, doctrine and jurisprudence have long admitted that equality between partners has only a relative scope. This one must be assessed ''in concreto'' and does not oppose unequal treatment between partners justified by the defense of the social interest or the existence of differences of situations. On the other hand, the legislator has gradually introduced into the law of companies many mechanisms having an inegalitarian function. This was the case with the old share classes, namely the priority shares, those with priority dividend without voting rights, investment certificates or voting certificates. The same is true of preferred stocks and special advantages. All these devices have the vocation of breaking the equality between partners, by providing to some of them, privileges not shared by others. However, the law largely allows, or allowed their institutionalization. In view of these observations, it became legitimate to question the existence of a right to discriminate between partners.Therefore, the ambition of this study is to demonstrate that inequality between partners enjoys general validity in companies. Clearly to construct a definition, to determine its legal foundations, the possibilities and limits, and the procedure for its creation and its disappearance, these were the elements that needed to be reflected in law in order to allow practitioners to approach discrimination between partners with more serenity.
Keywords: Actions de préférence; Associés; Avantages particuliers; Companies; Corporate law; Droit des sociétés; Désavantage particuliers; Equality; Inequality; Inégalité; Liberté contractuelle; Partners; Prefered stock; Sociétes; Special advantages; Égalité

Compra e venda de participações societárias de controle - Buschinelli, Gabriel Saad Kik (Universidade de São Paulo, 2017)
A compra e venda de participações societárias de controle é contrato de inegável relevância prática. Juridicamente, a sociedade permanece titular de seus bens. Economicamente, a transferência das participações societárias possui efeito similar à circulação dos ativos. É natural e intuitiva, portanto, a equiparação entre a alienação de quotas e de ações, de um lado, e a negociação da empresa, de outro. O estudo, porém, investiga os fundamentos e os limites das teorias que definem o regime do negócio jurídico com base na realidade econômica, defendendo sua inadequação. A tese sustenta que o contrato de compra e venda de participações societárias (i) é dotado de autonomia categorial; (ii) suscita problemas específicos, que devem ser assim analisados; e (iii) somente deve ser equiparado com outras formas de transmissão de bens integrantes do patrimônio de maneira excepcional e justificada. O trabalho é composto por cinco capítulos. No primeiro, questiona-se quais seriam os pressupostos metodológicos para o afastamento da personalidade jurídica societária. Assentadas as bases teóricas, passa-se, no segundo, à compreensão dos traços específicos que caracterizam o contrato. A partir de perspectiva funcional, o terceiro capítulo indaga a possibilidade de serem aplicados regimes jurídicos previstos para o trespasse de estabelecimento, para a transferência de imóveis ou para a cessão de posição contratual quando ocorre negociação de participações de controle de sociedade que seja titular desses bens. No quarto capítulo, são analisados o dever de informar e o ônus de se informar na fase pré-contratual. Ao final, é apresentado o regime de responsabilidade do vendedor e os mecanismos de tutela de que o comprador pode-se valer caso constate deformidades dos títulos ou dos elementos do patrimônio societário.
Keywords: Business establishment; Compra e venda; Contractual liability; Controle acionário; Corporate law; Duty to inform; Equity investments; Negócio juridico; Purchase and sale; Shares; Sociedade comercial; Société commerciale

L'intervention du juge dans la vie de la société en droit français et en droit OHADA - Mugisho Kazingufu, Jean-Jacques (Université de Goma, 2017)
Keywords: Corporate law; Droit des sociétés; Intérêt social; Règlement de conflits

A sociedade unipessoal de direito angolano : contributo para a compreensão do seu regime jurídico - Salvador, Gorki (Universidade de Lisboa, 2017)
A presente investigação tem como objecto a Sociedade Unipessoal de Direito angolano. Com o desenvolvimento da mesma, ambicionamos prestar um contributo para a compreensão do regime jurídico positivo da unipessoalidade no Ordenamento Jurídico angolano. É um facto que o reconhecimento legislativo da Sociedade Unipessoal representa o acompanhamento, pelo Direito, da evolução da realidade económica, estabelecendo-se assim a necessária correspondência entre a realidade e o Direito. É do mesmo modo um facto que a Sociedade Unipessoal contraria a dogmática básica do Direito Societário, assente na ideia de que sociedade é uma realidade de que apenas uma pluralidade de indivíduos pode fazer recurso, ao ponto de se considerar a sociedade constituída por uma única pessoa uma autêntica contradictio in terminis. Portanto, o reconhecimento da unipessoalidade societária como uma situação ordinária, para além de acrescentar valores próprios ao ordenamento jurídico-societário, levanta uma série de questões que vão desde a contradição terminológica aos problemas concretos que apenas se levantam na presença da sociedade unipessoal ou que nelas se levantam com mais acuidade. A análise problemática de algumas perplexidades que se levantam no âmbito da Sociedade unipessoal ocupa as páginas do presente estudo.
Keywords: Angola; Direito das sociedades; Sociedade unipessoal

Aspectos jurídicos do processo de formação de capital por meio do mercado de valores mobiliários: as alternativas de organização e capitalização das sociedades empresárias - Pitta, André Grünspun (Universidade de São Paulo, 2017)
O presente trabalho tem por objetivo avaliar o arcabouço jurídico e regulatório brasileiro relativo às formas de organização das sociedades empresárias e aos instrumentos de captação de recursos a elas disponíveis, de modo a verificar em que medida favorecem o processo de formação de capital por meio do mercado de valores mobiliários. Para tanto, são avaliados determinados aspectos associados à disciplina das sociedades empresárias e ao processo de captação de recursos, reputados relevantes sob a perspectiva do fomento à utilização do mercado de valores mobiliários para a formação de capital. O Capítulo 2 estabelece os elementos principais que justificam a pesquisa conduzida e as premissas adotadas na análise que se seguirá da disciplina jurídica que conforma o processo de formação de capital por meio do mercado de valores mobiliários. O Capítulo 3 analisa as estruturas jurídicas para organização das sociedades empresárias, com o objetivo de averiguar a natureza de determinados requisitos organizativos impostos como precondição para a utilização do mercado de valores mobiliários. Partindo de elementos advindos da teoria do contrato financeiro, busca-se analisar determinados aspectos da disciplina societária -- associados à alocação de direitos políticos e econômicos entre investidores e empreendedores, à estrutura decisória e administrativa da empresa e ao regime de destinação de seus resultados -- em relação aos quais um maior espaço para a autonomia privada é salutar à conformação dos arranjos subjacentes à relação de investimento que se estabelece entre investidores e empreendedores no âmbito do processo de formação de capital por meio do mercado de valores mobiliários. O Capítulo 4 trata de analisar as estruturas jurídicas e regulatórias que regem a captação de recursos por meio do mercado de valores mobiliários, especialmente a partir dos mecanismos de formação privada (private equity e venture capital), semipública (ofertas restritas, limitadas e dispensadas de registro) e pública de capital, com o objetivo de averiguar se as alternativas postas à disposição das sociedades empresárias e o balanceamento regulatório aplicável favorecem o processo de formação de capital por meio do mercado de valores mobiliários. Conclui-se, ao final, que a disciplina societária e do mercado de valores mobiliários brasileiro é dotada de elementos de rigidez e inflexibilidade em vários aspectos relevantes, especialmente em comparação com a disciplina norteamericana e europeia. A diminuição do espaço da autonomia privada em relação a tais aspectos pode afetar a atratividade do mercado de valores mobiliários enquanto alternativa de financiamento da atividade empresária.
Keywords: Capital formation; Capitalisation; Corporate law; Corporate structure; Formation de capital; Formação de capital; Marché des capitaux; Mercado de capitais; Securities market; Securities offers; Sociedade comercial; Société commerciale; Valeurs mobilières

A regra dos §§ 8º e 9º do art. 118 da Lei das S.A. e a possibilidade de abuso do poder de controle em companhias - Vilar, Bruno Haack (Universidade de São Paulo, 2017)
Esta tese trata do abuso do poder em companhias sob controle conjunto formado a partir da celebração de acordo de acionistas e o exercício das prerrogativas conferidas pelo art. 118, §§ 8º e 9º da Lei das S.A. aos acordantes e aos presidentes da assembleia geral e órgãos colegiados de administração da companhia. Seu objetivo precípuo é contribuir para a delimitação do risco de que tais prerrogativas sejam utilizadas para a prática de atos ilícitos. O tema é investigado dogmática e empiricamente - neste segundo caso, mediante um estudo de caso da capitalização de Oi S.A., realizada em 2014. No Capítulo I caracterizam-se o poder de controle conjunto e o acordo de acionistas sobre exercício do poder de controle. No Capítulo II, analisa-se o abuso do poder de controle, tanto no direito estrangeiro (escolhidos como paradigmas de análise os Estados Unidos da América e Reino Unido da Grã-Bretanha e Irlanda do Norte), quanto no brasileiro, e relaciona-se tal conceito ao de benefícios privados do controle (ou tunneling), desenvolvido por economistas. Por fim, no Capítulo III analisam-se as normas do art. 118, §§ 8º e 9º da Lei das S.A. Em cada um dos capítulos a análise dogmática é seguida de estudos empíricos que visam a aplicar os conceitos desenvolvidos ao caso estudado. Ao final, conclui-se que somente sob circunstâncias específicas os direitos e deveres decorrentes dos §§ 8º e 9º do art. 118 podem servir de instrumento ao abuso do poder de controle - quando não houver incentivos para que os acordantes cheguem a uma solução negociada, evitando os conflitos que levariam à aplicação de tais dispositivos. This thesis addresses the abuse of control power by controlling shareholders in companies under joint control based on a shareholders' agreement and the use of the faculties granted by Section 118, §§ 8th and 9th to the parties to shareholders' agreement and the chairmen of the general meeting and boards of the company. Its main objective is to contribute to delimitation of the risk of use of such faculties for the practice of illicit acts. The theme is analysed both dogmatically and empirically - in the latter case, via a case study of the capitalization of Oi S.A., which took place in 2014. In Chapter I joint control and shareholders' agreements for the exercise of control power are defined. In Chapter II, the abuse of control power is examined, both in foreign law (chosen analytical paradigms are the United States of America and the United Kingdom of Great Britain and Northern Ireland), and in Brazilian law, and said concept is related to that of private benefits of control (or tunnel - ling), as developed by economists. Finally, in Chapter III the rules of Section 118, §§ 8th and 9th of the Companies Act are reviewed. In each chapter dogmatic analysis is followed by empirical studies which aim at applying the concepts developed to the case studied. By the end, it is concluded that only under specific circumstances the rights and duties arising from §§ 8th and 9th of Section 118 may work as instruments for the abuse of control power - whenever there are no incentives for the parties to the shareholders' agreement to reach a negotiated solution, avoiding the conflicts that would lead to employment of said provisions.
Keywords: Abuse of control power; Abuso de poder; Brasil; Case study; Company; Control power; Controle acionário; Direito Comercial; Direito Comparado; Estados Unidos; Grã-Bretanha; Oi S.A.; Shareholders' agreements; Sociedade por ações

Sociedade criada de facto e sociedade de facto no direito da OHADA : estudo comparativo jurisprudencial entre o direito brasileiro e português - Silva, Osvaldo Júlio da (Universidade de Lisboa, 2017)
A presente dissertação de Mestrado visa analisar e apresentar uma reflexão mais abrangente e aprofundada sobre a problemática inerente às sociedades criadas de facto e sociedades de facto no Direito da OHADA, nunca antes tratada pela doutrina nacional e (ou pela doutrina da OHADA) especializada, cujo resultado final esperamos poder contribuir, em certa medida, para o reforço da segurança jurídica e judiciária nos Estado-Membros da OHADA. As sociedades criadas de facto e sociedades de facto podem perturbar (e, efetivamente, perturbam) o exercício legítimo de atividades comerciais, uma vez que geram a insegurança jurídica e judiciária para investidores e para o comércio em geral. Com efeito, trata-se de realidades societárias, por vezes, constituídas e dissolvidas à margem do quadro legal vigente. À luz do artigo 98.º do Ato Uniforme Relativo as Sociedades Comerciais (AUS), todas as sociedades comerciais adquirem a personalidade jurídica a partir da sua matrícula no Registo do Comércio e do Crédito Mobiliário. Por isso, a maior parte da doutrina tem perdido demasiado tempo e energia na exegese deste preceito, deduzindo nele o efeito constitutivo do registo. Porém, temos para nós que a génese da sociedade reside na vontade das partes, tendo o registo o efeito principal de atribuição de um privilégio comercial de limitação da responsabilidade. Todavia, o registo não deixa de ser condicionante da plenitude da personalidade. A sociedade resulta de um contrato e não, necessariamente, do mero facto. This Master's thesis aims at analyzing and providing with a broadly and in-depth reflection on the problems connected to the partnership by estoppel and partnership de facto in OHADA Law, never before analyzed by national doctrine and (or OHADA doctrine). The final outcome of which we hope will contribute, at certain point, to the strengthening of legal and judicial certainty in the Member States of OHADA. Partnership de facto and partnership by estoppel may disturb (and, indeed, disrupt) the legitimate exercise of commercial activities, since they create legal and judicial uncertainty for investors and for trade in general. In fact, these corporate realities are sometimes constituted and dissolved out of the legal framework in force. Pursuant to the OHADA Uniform Act Relating to Commercial Companies and Economic Interest Group (UACC/EIG), registration is mandatory and companies only have legal personality as from the date of registration of the By-laws with the Registry of Companies. Thus, most of the doctrine has spent too much time and energy in the exegesis of this precept, deducing in it the constitutive effect of the register. As far as we are able to judge, the genesis of society lies in the will of the parties, and registration has the main effect of conferring a commercial privilege on limiting liability. However, it does not cease to be a condition of the fullness of personality. The company results from a contract and not necessarily from the mere fact.
Keywords: Direito comercial; OHADA; Sociedade comercial

Intervenção judicial na administração de sociedade: nomeação de interventor provisório - Vidal Neto, Ademar (Universidade de São Paulo, 2017)
A tese propõe a sistematização da intervenção judicial na administração de sociedades no Brasil. Para tanto, adotou-se um conceito restritivo de intervenção judicial, assim consideradas apenas as hipóteses em que o magistrado nomeia interventor provisório (terceiro estranho ao quadro social) para integrar-se à administração da sociedade. Existem diversas modalidades de intervenção -- da mais branda (nomeação de interventor-observador) à mais incisiva (nomeação de interventor-administrador) --, devendo o juiz eleger a que melhor atenda às necessidades do caso concreto. A aplicação do instituto deve ser encarada como medida excepcional, última alternativa, diante das graves consequências que pode produzir, circunstância que não pode e não deve, todavia, impedir a sua utilização sempre que necessário (manejada de forma adequada, a intervenção pode ser de grande valia para a solução do conflito societário). The thesis proposes the systematization of the judicial interference in the management of companies in Brazil. For that purpose, a restrict concept of judicial interference was adopted, considering as so solely the situations in which the judge appoints a temporary intervenor (a third party outside of the company's bodies) to integrate itself to the company's management. There are several types of interference - from the softer ones (appointment of an observing intervenor) to the stronger ones (appointment of a managing intervenor) -, being up to the judge to select the one that best suits the necessities of the specific case. The use of the institute should be faced as an extraordinary measure, a last resource, due to the serious consequences it can produce, circumstances which, however, should not and shall not prevent its use when necessary (if managed adequately, the interference can be of great value to the resolution of corporate conflicts).
Keywords: Appointment of temporary intervenor; Choice of the intervenor; Civil liability; Control mechanisms; Corporate conflicts; Direito Comercial; Interference decree; Judicial interference; Principle of the minimum interference; Responsabilidade civil; Sociedade comercial

La fiscalité des groupes de sociétés : étude comparée - Boumeddane, Zaza (Université d'Oran 2 Mohamed Ben Ahmed, 2017)
La fiscalité des groupes de sociétés intéresse le monde des affaires et tout contribuable. Le régime fiscal des sociétés est très incitatif à la création de groupes. Cela dit, c’est un régime fiscal récent en Algérie, son application nécessite des conditions. Il peut faire l’objet d’une révision. Le code fiscal algérien s’est ressourcé beaucoup du Code General des Impôts français. La détermination du résultat fiscal d’ensemble est restée une très grande problématique. Le résultat fiscal nécessite différents retraitements. Les transferts de bénéfices et le régime des restructurations donnent eux aussi droit à des impositions. Le régime de consolidation fiscale vise avant tout l’impôt sur les bénéfices des sociétés, cela dit les droits d’enregistrements, la taxe sur la valeur ajoutée, les cas de cessation du régime et les cas de sortie entrainent elles aussi des retraitements. Le groupe de sociétés peut être soumis à un contrôle fiscal en cas d’anomalies dans les déclarations fiscales. Company group’s taxation interests the business world and every taxpayer. Companies’ fiscal regime is very incentive to company creation. This type of regime is recent in Algeria. Its application regimes conditions, it is susceptible of revision. Algeria’s fiscal code has taken much from France’s general fiscal one. The determination of overall tax result is still a very large problematic. Tax result requires different adjustments. The transfer of profits and the regime of restructuring gives right to taxation. The tax consolidation regime aims primarily at taxing companies on their profits. Registration fees, the added tax value and cases of regime cessation, and cases of output causes retreatment. Company groups may be subject to tax control in case of anomalies in tax declaration.
Keywords: Account consolidation; Acte anormal de gestion; Consolidation des comptes; Consolidation fiscale; Division of taxation; Droit des sociétés commerciales; Fiscal consolidation; Fiscalité; Fiscalité des apports partiels d’actifs; Fiscalité des fusions; Fiscalité des scissions; Group of companies; Groupe de sociétés commerciales; Management act; Opérations de restructuration; Result owerall taw; Régime fiscal; Résultat fiscal d’ensemble; Tax; Tax asset partial contributions; Tax regime for restructuring commercial companies; Tax treatment of abnormal; Taxation of mergers; Taxe sur la valeur ajoutée; Transfer of profits to abroad; Transfert de bénéfices vers l’étranger; Value added tax

La acción social de responsabilidad - Cerezuela Moraleja, Alejandro (Universidad Internacional de Andalucía, 2017)
Trabajo Fin de Curso de Experto Universitario en Derecho Societario (2016/17). Tutora: Dra. Patricia Márquez Lobillo. Ante la conducta por la que el administrador social causa un daño al patrimonio de la sociedad, la Ley de Sociedades de Capital ofrece un mecanismo por el cual poder exigirle la reparación del daño, mediante la acción social de responsabilidad, que podrá ser ejercida por la sociedad, los socios o terceros, con la finalidad de restablecer el patrimonio social. Este trabajo nace con la intención de ofrecer un enfoque práctico para el ejercicio de la acción, estudiando los elementos necesarios que han de cumplirse en cada uno de los legitimados para poder ejercitarla eficazmente y cómo actuar frente a la acción por quien no esté de acuerdo a su ejercicio. Para todo ello se apoya el trabajo en la jurisprudencia más actual y relevante en cada supuesto.

L’incidence des risques familiaux sur la société entre époux dans l’espace OHADA - Djoupoyang Igri, Gaston (Revue libre de Droit, 2017)
Keywords: Divorce; Epoux; Mésentente; Patrimoine; Risques familiaux; Société entre époux

Sınır aşan şirket birleşmelerine uygulanacak hukuk - Kavlak, Bengül (Dokuz Eylül Üniversitesi, 2017)
Son yıllarda, uluslararası ticaret hukukundaki gelişmelerle birlikte sınır aşan şirket birleşmeleri de giderek önem kazanmıştır. Şirketler bakımından yabancı bir şirketle birleşmenin getirdiği pek çok avantaj yanında, çeşitli zorluklar da mevcuttur. Bu zorluklardan en önemlilerinden bir tanesini de sınır aşan birleşmelere uygulanacak hukukun tespiti oluşturmaktadır. AB hukukunda, sınır aşan şirket birleşmelerine ilişkin düzenlemeler öngörülerek üye devletler arasındaki uygulamanın yeknesaklaştırılması adına 2005/56/EC sayılı Direktif kabul edilmiştir. Türk hukuku bakımından ise, sınır aşan şirket birleşmelerinin önemine vurgu yapılmakla birlikte bu hususta henüz bir düzenleme getirilmiş değildir. Çalışmada, AB hukukunda bu hususta öngörülen düzenlemeler de değerlendirilmek suretiyle, Türk hukukunda sınır aşan şirket birleşmelerine uygulanacak hukukun tespiti üzerinde durulmuştur. Sınır aşan şirket birleşmelerine uygulanacak hukuka ilişkin görüşler de değerlendirilerek, AB hukuku ile de uyum sağlamak adına, Türk hukukunda her bir birleşme işlemi için uygulanacak hukuk değerlendirilmiş ve sınır aşan şirket birleşmelerine uygulanacak hukuka ilişkin düzenleme önerisinde bulunulmuştur. Anahtar Kelimeler: Sınır aşan birleşme, uygulanacak hukuk, şirket birleşmeleri, 2005/56/EC, AB hukuku. With the recent developments in international commercial law, cross-border mergers have been developed during the last few decades. Besides the advantages of merging with a company from a different country, there are also some difficulties especially about determining the applicable law. In European Union, Directive 2005/56/EC of the European Parliament and of the Council of 26 October 2005 on cross-border mergers of limited liability companies has been accepted to regulate this issue and harmonise the rules of substantive law of the member states. In Turkish law, despite the emphasize on the significance of the cross-border mergers at the preamble of Turkish Commercial Code, currently there is no codification about cross-border mergers. This study attempts to make a discussion about the applicable law to cross-border mergers from the perspective of Turkish law and a comparison between the regulations of European Union law and Turkish law. Yet, taking into consideration the EU-Turkey relations and the developments about the adaption of Turkish law to European Union law, the harmonization of rules about cross-border mergers must be inevitable. As the applicable law to cross-border mergers is topical and important subject for Turkish law, the study will also deal with the legislation proposal in accordance with European Union law. Key Words: merger, cross-border merger, applicable law, 2005/56/EC, EU law.
Keywords: Avrupa Birliği hukuku; Birleşmeler; European Union law; Fusion d'entreprises; Intenational strategical mergers; International Law; International enterprises; International integrations; Mergers; Uluslararası Hukuk; Uluslararası bütünleşmeler; Uluslararası işletmeler; Uluslararası stratejik birleşmeler; Şirket birleşmeleri

Kurumsal yönetim ilkeleri bakımından halka açık anonim şirketlerde icrada görevli olmayan yönetim kurulu üyeleri - Küçükgüngör, Makbule Asli (Ankara Üniversitesi, 2017)
In publicly held companies where the shareholdership is differentiated from the control and the management of the company, the dispersed shareholding structure prevents the active involvement of the shareholders in the company management while the directors have the opportunity to act in their personal interests. The aforementioned conflict of interest between the shareholders and the directors in the management of the publicly held companies which has been identified as "Principle-Agent Problem" in economic literature has had substantial effect in modern company law. Accordingly, considerable work in the company law has been dedicated to the legal strategies developed to decrease the cost of monitoring directors for shareholders. One of the main corporate governance strategies that is developed to deal with the "Principle-Agent Problem" focuses on increasing the number and the effectiveness of the directors who are not involved in the managing activities of the company. The main principle of this legal strategy is the designing the structure of the board of directors on the basis of team spirit and mutual accountability. In that sense, non-management directors conduct their duties as directors without having management tasks in the company. As these directors work on a part time basis they are not fully depended to the company and in principle they receive symbolic amounts of remuneration. Under this incentive strategy it is accepted that the esteem and reputation that the non-management directors preserve in eye of the public are the main incentives that motivate them to monitor the managing directors. The corporate governance principles are designed as alternative to the rule based regulation approach in company law. The non-management directorship which is introduced as a corporate governance concept for solving the problem of conflict of interest between the shareholders and the directors is the focus area of this thesis. The thesis consists of five parts. In the first part of this study, the concept of corporate governance which is the source of non-management director concept and the conflict of intererest problem between the shareholders and the directors regarding the management of the publicly held companies have been introduced. In this regard, "Centralised Management" and "Principle-Agent Problem" are explained. Finally, based on the "Principle-Agent Problem" the legal theories that are developed to increase the effectiveness of the board of directors, the categorisation of those strategies that has been introduced and place of the non-management directors among those strategies are clarified. In the second part the emergence of the concept of non-management directorship system and the development of the mechanisms for increasing director independence are described and different forms of non-management directors in one-tier board structures are analysed. On this subject the legal designing of the concepts of independent and disinterested directorship which is developed in American law and non-executive directorship which is introduced in the British Law is analysed. In the third part, the concept of the supervisory directorship which corresponds to the non-management directorship in two-tier board system is examined. Forth part of the thesis focuses on the comparison of one-tier and two-tier board structures in application of the non-management directorship concept. Within this scope, it has been analysed whether there is a convergence in the functions of non-management directors in terms of supervision, strategy development and networking in the two types of board systems. Related to this analysis, the effectiveness of the non-management directors in one-tier and two-tier board systems and the role of the institutional investor regarding this effectiveness is evaluated. In recent years, depending on the inclination of convergence in different law systems, there has been an alignment effort in the European Union to have a single set of rules regarding the non-management directors. In this respect as a final focus point, in this part, the regulations of the European Union regarding the non-management directors are examined. The fifth part is dedicated to legal design of the independent directorship which is regulated under the non-management directorship concept in the Turkish law. Turkish Commercial Code is the general code that regulates all joint stock corporations including the publicly held ones. Therefore in order to explain the effects of Anglo-American approach on the administrative organ, the approach of the Turkish Commercial Code regarding the structure and functioning of the board of directors which are based on corporate governance principles are explained. Following that general introduction, the system change regarding the corporate governance principles in Turkey which consists of application of mandatory rules rather than "Comply or Explain" approach that is applicable to independent directors is explained. After that the independence criteria which are set for the independent directors under the capital market regulations for publicly held joint stock corporations and the role of independent directors in decision making mechanism are analysed. Finally, the structure and functioning of the board committees are evaluated by examining the functions of the independent board members.
Keywords: Bağımsız idari otoriteler; Commercial law; Corporate governance; Halka açık ortaklıklar; Independent administrative authority; Kurumsal yönetim; Management; Members of the board directors; Principle; Public held companies; Representation; Ticaret hukuku; Vekalet; Yönetim; Yönetim kurulu üyeleri; İlke

Anonim ortaklık genel kurul toplantılarında pay sahibinin temsili - Tekten, Emel (Erciyes Üniversitesi, 2017)
Pay sahipleri genel kurula katılma maliyetlerinin fazla gelmesi, buna ayıracak zamanlarının olmaması veya sağlık sorunları gibi sebeplerle dolayı genel kurula katılmak istemeyebilir. Bunun sonucunda pay sahiplerinin şirketin işleyişine ve genel kurul kararlarına etki etme olasılıkları zayıfladığından; genel kurullarda, etkin ve iyi organize olmuş pay sahipleri gerçekte çoğunluk olmasalar da istedikleri kararların alınmasını sağlayabilmektedirler. Bu durum genel kurulda güç boşluğu sorununun doğmasına neden olmaktadır. Bu kapsamda anonim şirket genel kurulunda pay sahibinin temsilinin bu konudaki sorunları giderme de önemli bir rolü vardır. İşte tezimizin konusu, TTK ve SerPK çerçevesinde anonim şirket genel kurulunda pay sahibinin temsilidir. Bilindiği üzere 6102 sayılı TTK bir bütün olarak 01.07.2012 tarihinde yürürlüğe girmiş ve böylece elli yılı aşkın bir süredir uygulanan 6762 sayılı eTTK'yı yürürlükten kaldırmıştır. Yine 6362 sayılı SerPK 30.12.2012 tarihinde yürürlüğe girerek 2499 sayılı SerPK'yı yürürlükten kaldırmıştır. Bu yeni kanunlarda tez konumuzla ilgili olarak bir dizi değişiklikler yapılmış ve yenilikler getirilmiştir. Tez konusunun seçilmesindeki amaç, pay sahibinin temsiliyle ilgili olarak TTK ve SerPK mevzuatlarında getirilen yeni düzenlemelerin Yargıtay kararları, öğretideki görüşler ve mukayeseli hukuk ışığında değerlendirerek olası problemler karşısında çözüm önerileri getirip Türk Hukukuna katkı sağlamaktır. Bu tez çalışmasının ortaya konulması sırasında özellikle konuya kaynaklık eden İsviçre Hukuku ve literatüründen faydalanılmıştır. Konu, Türk Hukuku bakımından incelenirken İsviçre Hukukundan farklılıkları ve benzerlikleri ortaya konulmaya çalışılmıştır. Bunun dışında konumuzla ilgili olarak Alman, Amerikan, İngiliz ve Avrupa Birliği Hukuklarından da yararlanılmıştır. Yapılan değerlendirmeler sonucunda birçok sonuçlar elde edilmiştir. Ancak özellikle şunu belirtmeliyiz ki; halka açık anonim ortaklıklar düşünülerek getirilen TTK m. 428'de ifade edilen toplu temsilciler ile ilgili düzenleme, SerPK m. 30/4'te ve SPK II-30.1 sayılı Tebliğ m. 5/3 düzenlemeleri sebebiyle uygulanmayacaktır. Üstelik bu hükümler nedeniyle Türk Ticaret Kanunu ile Bazı Kanun ve Kanun Hükmünde Kararnamelerde Değişiklik Yapılmasına Dair Kanun Tasarısı Taslağı m. 12'de TTK m. 428, 430 ve 431 hükümlerinin yürürlükten kaldırılması öngörülmektedir. Getiriliş amacı geniş kitlelerin temsilini sağlamak olan bu hükümleri yürürlükten kaldırmak yerine, SerpK'nın ilgili hükümleri ile gerekli koordinasyon sağlanarak, bunların tüm ortaklıklar yönünden uygulanmasının yolu açılmalıdır. Anahtar Kelimeler: Anonim Ortaklık; Genel Kurul; Pay Sahibi; Temsil. Shareholders may refrain to join general assembly meetings due to the reasons like participation costs, lack of time and health issues. Since the possibility of the shareholders to have an impact on the functioning of the company and its general assembly gets weakened as a result of non-attendance, active and well-organized shareholder groups-despite the fact that they do not constitute the majority of the shareholders- may achieve their desired general assembly decisions. This particular issue causes an occurrence of a power gap in general assemblies. In this context, representation of the shareholders in the general assembly of the joint stock companies plays a role of utmost importance in eradicating such problems. Hence, the topic of my thesis is the representation of the shareholders in the general assembly of the joint stock companies within the legal framework of Turkish Commercial Code and Turkish Capital Market Code. As known, Turkish Commercial Code No. 6102 came into force in 01.07.2012, repealing former Turkish Commercial Code No. 6762 which was in force for more than fifty years. Also, Turkish Capital Market Code no. 6362 came into force in 30.12.2012, repealing former Turkish Capital Market Code no. 2449. There has been a series of amendments performed on those two codes concerning my thesis topic. My main goal on choosing this topic is to contribute to Turkish Law through assessing those amendments in the light of supreme court orders, scientific opinions and comparative law and to provide solutions to the existing and prospective problems. In preparation of this work, apart from Turkish Law, Swiss Law is highly referenced as it constitutes the main source of the issue. Therefore, while assessing the point, similarities and differences between Turkish and Swiss law is asserted. Besides, German Law, European Union Law, American Law and English law are also referenced for the sake of the proper assessment of the topic. As a consequence of made analyzes, a lot of conclusions are drawn. However, it is to be pointed out particularly that the regulations in Turkish Commercial Code No. 6102 article 428 which were provided considering open joint stock companies will not be applied because of Turkish Capital Market Code No. 2449 article 30/4 and the regulation of Turkish Capital Market Board no. II-30.1 article 5/3. Moreover, because of those provisions, repealing of the articles no. 428,430,431 of Turkish Commercial Code no. 6102 is at stake. Instead of repealing those provisions of Turkish Commercial Code no. 6102 -which aim at representation in a broader sense- establishing the coordination between those provision and related Turkish Capital Market Code provisions and enabling the application of those provisions on all sort of companies must be done. Keywords: Joint Stock Company, General Assembly, Shareholder, Representation
Keywords: Actionnaires; Anonim ortaklıklar; Assemblée générale; Consumer right to representation; Genel kurul; Genel kurul kararları; General assembly; General assembly resdutions; Incorporated companies; Meetings; Pay sahipleri; Representation; Représentation; Shareholders; Temsil; Temsil edilme hakkı; Toplantılar; Turkish Commercial Code; Turkish commercial law; Türk Ticaret Kanunu; Türk ticaret hukuku

Pay sahipleri sözleşmesinden doğan birlikte satma hakkı ve birlikte satışa zorlama hakkı - Yilmaz, Gülşah (Dokuz Eylül Üniversitesi, 2017)
Birlikte satma hakkı ve birlikte satışa zorlama hakkı pay sahipleri sözleşmesinde yer alan iki haktır. Bu hakların kaynağı Amerikan hukukudur. Bu haklar ülkemizde anonim şirket esas sözleşmelerinde sıklıkla yer almaktadır. Bu çalışmada Amerikan hukukundan gelen bu haklar Türk Ticaret Hukuku kuralları açısından incelenmiştir. İnceleme yöntemi ilk olarak hakların tanıtılması ikinci olarak ortaya çıkardığı hukukî ilişkinin niteliğinin tespiti ve son olarak hukukumuza ait yasal düzenlemeler karşısında ne derece geçerli kabul edilebileceğinin belirlenmesi şeklindedir. Çalışmada, hakların karşılaştırmalı hukuktaki yeri incelenmiştir. Bu kapsamda yabancı mahkeme kararları ve yasal düzenlemeler hakkında bilgi verilmiştir. Akabinde hakların hukukî niteliği ve haklardan doğan borçlar incelenmiştir. Son olarak hakların anonim ve limited şirket sözleşmelerinde yer alması durumunda meydana gelebilecek hukukî sorunlar tartışılmıştır. Bu kapsamda hakların yarattığı pay devir sınırlandırmasının anonim şirketler hukukunda yer alan kurallar karşısındaki durumu incelenmiştir. Ayrıca hakların limited şirketlerde pay devri ile ilgili düzenlemeler açısından geçerliliği tartışılmıştır. Anahtar Kelimeler: Birlikte Satma Hakkı, Birlikte Satışa Zorlama Hakkı, Pay Devrinin Sınırlandırılması, Pay Sahipleri Sözleşmesi, Anonim Şirket Esas Sözleşmesi. Tag along right and drag along right are two rights in shareholders' agreement. The source of these rights is American Law. These rights are frequently found in the articles of association of the joint stock company in our country. In this study, these rights coming from American law were examined in the terms of Turkish Commercial Law. The examination method is firstly the identification of the rights, secondly the determination of the nature of the legal relationship that emerges from the rights and finally the determination of the extent to which they can be regarded as valid under the legal regulations of our law. In the study, the position of the rights in comparative law were examined. In this context, information is given about the foreign court decisions and legal regulations. Then the legal nature of the rights and the obligations arising from the rights were examined. Finally, the legal issues that may arise in case of the rights are included in joint stock company and limited company contracts are discussed. In this context, the situation of the share transfer restrictions created by the rights against the rules in the corporation law has been examined. Furthermore, the validity of the rights in terms of the share transfer regulations in limited companies has been discussed. Keywords: Tag Along Right, Drag Along Right, Share Transfer Restriction, Shareholders' Agreement, Article Of Association.
Keywords: Actionnaires; Anonim şirketler; Birlikte satma hakkı; Birlikte satışa zorlama hakkı; Birlikte vekalet; Drag along righ; Joint agency; Joint stock company; Pay devri; Pay sahipleri; Sale; Sales contracts; Sales methods; Satış; Satış sözleşmeleri; Satış yöntemleri; Shareholders; Tag along righ; Transfer of shares; Vente conjointe; Vente forcée